Taxonomic reinvestigation of the genus Tetradesmus (Scenedesmaceae; Sphaeropleales) based on morphological characteristics and chloroplast genomes - Cho, Hyeon Shik; Lee, JunMo (Frontiers in Plant Science, 2024)
The genus Tetradesmus (Scenedesmaceae; Sphaeropleales) comprises one of the most abundant green algae in freshwater environments. It includes morphologically diverse species that exhibit bundle-like, plane-arranged coenobia, and unicells, because several different Scenedesmus-like groups were integrated into this genus based on phylogenetic analysis. Nevertheless, there is no clear information regarding the phylogenetic relationship of Tetradesmus species, determined using several marker genes, because of low phylogenetic support and insufficient molecular data. Currently, genome information is available from diverse taxa, which could provide high-resolution evolutionary relationships. In particular, phylogenetic studies using chloroplast genomes demonstrated the potential to establish high-resolution phylogenetic relationships. However, only three chloroplast genomes are available from the genus Tetradesmus. In this study, we newly generated 9 chloroplast genomes from Tetradesmus and constructed a high-resolution phylogeny using a concatenated alignment of 69 chloroplast protein sequences. We also report one novel species (T. lancea), one novel variety (T. obliquus var. spiraformis), and two novel formae (T. dissociatus f. oviformis, T. obliquus f. rectilineare) within the genus Tetradesmus based on morphological characteristics (e.g., cellular arrangements and coenobial types) and genomic features (e.g., different exon–intron structures in chloroplast genomes). Moreover, we taxonomically reinvestigated the genus Tetradesmus based on these results. Altogether, our study can provide a comprehensive understanding of the taxonomic approaches for investigating this genus.